2008
DOI: 10.1103/physrevlett.100.100501
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantum Critical Points by a Probe Qubit

Abstract: Quantum phase transitions occur when the ground state of a quantum system undergoes a qualitative change when an external control parameter reaches a critical value. Here, we demonstrate a technique for studying quantum systems undergoing a phase transition by coupling the system to a probe qubit. It uses directly the increased sensibility of the quantum system to perturbations when it is close to a critical point. Using an NMR quantum simulator, we demonstrate this measurement technique for two different type… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 31 publications
2
87
0
Order By: Relevance
“…Alternatively, fidelity susceptibility can also be obtained from the overlap of quantum many-body wave functions, which has been measured in a NMR quantum simulator [96] and, notably, in ultracold bosons by utilizing a quantum gas microscope [97]. Combining these detection approaches with recent efforts of realizing Kondo physics in ultracold atomic gases [19][20][21][22], the proposed diagnostic The data are the same as in Fig.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 4 Decembmentioning
confidence: 99%
“…Alternatively, fidelity susceptibility can also be obtained from the overlap of quantum many-body wave functions, which has been measured in a NMR quantum simulator [96] and, notably, in ultracold bosons by utilizing a quantum gas microscope [97]. Combining these detection approaches with recent efforts of realizing Kondo physics in ultracold atomic gases [19][20][21][22], the proposed diagnostic The data are the same as in Fig.…”
Section: H Y S I C a L R E V I E W L E T T E R S Week Ending 4 Decembmentioning
confidence: 99%
“…This coupling competes with the Zeeman energy being proportional to the geomagnetic field, and leads to a QPT at the critical point λ = 1. A central spin uniformly coupled with each spin in this TFI system possesses the dynamic sensitivity described by the sharp decay of LE near the QPT [22], which has been experimentally verified [20,23,24].…”
Section: Fig 1: (Color Online)mentioning
confidence: 67%
“…But the experiments [20,23,24] however demonstrated that even for N = 2, there still exists the dynamic sensitivity induced by quantum criticality. This result implies that dynamic sensitivity may have a close relation with the level crossing.…”
Section: Fig 1: (Color Online)mentioning
confidence: 99%
“…Recent investigations show that the LE may be employed to characterize QPTs since it has been found to have extra-fast decay in the vicinity of the critical points [42,[50][51][52][53][54]. Furthermore, as shown in Refs.…”
Section: Lochmidt Echo and Fidelity For The Dicke Model At Qptmentioning
confidence: 99%